ECRASEMENTS DE MEMBRES DE L’ENFANT MEMBER’S CRUSH INJURIES IN CHILDREN - Gnassingbe K; Walla A; Mihleudo-Agbolan K; Simkpa E; Goudjo E; Ndougssa I; Akakpo-Numado G K; Tekou H (European Scientific Journal, ESJ, 2015)
Objective: To describe the epidemiology, mechanisms of occurrence and therapeutic management of the crushing member’s injuries in children. Materials and methods: It was a retrospective study of the records of patients less than 15 years treated in the Pediatric Surgery Department of the Sylvanus Olympio teaching hospital (Lomé) for crushing members from January 2008 to December 2011. Results: We recorded 15 cases of crushing member’s injuries in children representing 1.7% of hospitalizations for trauma in the pediatric surgery department. The annual incidence was 3.7 cases. There were 7 males and 8 females. The average age of the patients was 8.8 years. Older children accounted for 10 cases (66.7%). Occurrences of accidents were the mechanisms of the public highway with 53.3% (8 cases) and 46.7% (7 cases) for domestic accidents. Five (5) patients had hemodynamic shock at admission. Treatment was radical in 10 patients (66.7%). It was an amputation. Conservative treatment consisted to the cast immobilization in three patients and intra focal osteosynthesis in two (2) patients. A suppuration of amputation stumps was recorded. The average length of hospital stay was 23.17 days (extremes: 1 and 60 days). Conclusion: Members’ crush injuries are relatively uncommon in pediatric units in Togo.